"Case report: First Record of Human Myiasis caused by Chrysomia bezziana (Villeneuve) in Iran (Diptera, Calliphoridae)" - S Tirgari; M Nateghpour; AH Jahanian; K Akbarzadeh (Tehran University of Medical Sciences, 2003)
A 45 year old farmer from Espand village (located in the west of Iranshahr county, Sistan and Baluchistan Province, southeastern of Iran) with some clinical manifestations referred to the Khatam-Al-Anbia Hospital in the city of Iranshahr. CT scan showed an extensive edema in nasal and para nasal sinuses. Endoscopy consideration revealed the presence of numerous larvae lodged inside the nasal cavity. Our precise investigations indicated that the flies were the old world screwworm (Chrysomia bezziana) according to the morphological characters of adult flies and full grown larvae.